Home sweet murder [large type] : true-crime thrillers - Patterson, James, 1947-; Bourelle, Andrew; Slaven, Scott (Thorndike Press, a part of Gale, a Cengage Company, 2018)
Two true-crime tales relate the stories of a couple who were tortured and left for dead after a home invasion, and a double homicide in Omaha, Nebraska.